Fostering sustainable development through adolescent engagement in vocational education - Aggarwal, Vandana; Rather, Mohd; Mehndroo, Meghna (Journal of Interdisciplinary Studies in Education, 2024)
In this study, we evaluate the effectiveness of vocational education and training (VET) in linking education outcomes to employment needs, with a focus on integrating industry-specific internships into VET curricula. This research highlights a disparity in the perceived value of VET, especially among women, indicating a broader sociocultural issue. Results indicated a gap in understanding VET’s role in sustainable development, suggesting a need for public awareness and policy reforms. We recommend modernizing VET systems to align more closely with economic and societal needs, involving the private sector and enhancing vocational curricula with practical experience. This study provides actionable insights for educational policy and administrative reform.